The Role of Self-Compassion and Psychological Well-Being Toward Non-Suicidal Self Injury - Hidayati, Farida; Mulyani, Sri; Fanani, Mohammad; Novitasari, Kristi Tamara (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
NSSI is an act of injury carried out intentionally and directly on body tissues without suicidal intent. Students have a vulnerability to doing this. An anonymous self-report survey was completed by 221 college students. Measurement using the Self Compassion Scale (α = 0.910) Well-being was measured using the Riff's Psychological Well-Being Scale (RPWB) and NSSI using ISAS (α = 0.910). Participants reported having injured themselves in 50% (n=107). The first onset of NSSI averaged 14.13 years. Participants aged 21-22 reported the highest incidence of self-harm in the past year (56%). The incidence in women is higher (80%). Women said more hair pulling (59%) while men hit themselves. (70%). Low self-compassion and psychological well-being significantly increase the possibility of NSSI in students. For this reason, protection factors need to be developed for students to empower themselves to prevent and avoid delays that harm them.